La lúdica en la enseñanza y aprendizaje de las Ciencias Naturales del Séptimo "A", de la Unidad Educativa Fiscomisional "La Dolorosa", 2021-2022 - Ochoa Cevallos, Carolina Alejandra (2022)
The present research work called: Playfulness in the teaching and learning of Natural Sciences, had as general objective to contribute significantly in the process of teaching and learning in the subject of Natural Sciences, through playfulness in the students of the Seventh "A" of the Fiscomisional Educational Unit "La Dolorosa", which integrated three specific objectives, To determine the theoretical foundations of playfulness within the teaching and learning process in the subject of natural sciences in order to identify the main significant contributions within the classroom and thus to elaborate a didactic guide that contributes to the improvement of the teaching and learning process in the natural sciences by potentiating playfulness. This study is descriptive with a non-experimental design implementing a mixed approach in order to describe in detail the phenomenon studied; likewise it was based on analytical, deductive, inductive and synthetic methods; followed by the following techniques were used: direct observation, survey and interview; considering the following instruments: observation sheet and questionnaire; which were applied to both the teacher and the seventh grade students, allowing to collect relevant information on the subject under investigation and then analyze and interpret them; having as conclusive results that: Playfulness creates dynamic and innovative spaces where students learn with ease the different contents and thus create pleasant experiences, likewise allows students to demonstrate their abilities, skills, imagination, knowledge, creativity, among others that contribute to the integral formation of each individual; finally it was decided to make a didactic guide that benefits the teaching and learning in the subject of natural sciences and thus the teacher uses them when required and innovates the educational process. Key words: Playfulness, Teaching, Learning, Natural Sciences.